2008
DOI: 10.1007/s10554-008-9341-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal left ventricular systolic function is impaired in patients with coronary slow flow

Abstract: Slow coronary flow (SCF) is a well recognized clinical entity, characterized by delayed opacification of coronary arteries in the presence of normal coronary angiogram. There is currently no data evaluating myocardial systolic function in SCF phenomenon. This study was performed to evaluate regional and global systolic function using tissue Doppler imaging (TDI), strain (S) and strain rate imaging (SRI) in patients with slow coronary flow. A total of 35 patients with slow coronary flow and otherwise normal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
2
21
1
3
Order By: Relevance
“…Studies on tissue Doppler imaging (pulsed wave or color coded) indices in patients with the coronary slow flow phenomenon have yielded different results. Although all of these studies were in agreement regarding a′ inasmuch as they reported no difference between patients with the coronary slow flow phenomenon and control groups, some of them showed that s′ and e′ were different between the groups, 13 , 14 , 17 , 18 , 24 and others revealed no difference between the groups 15 , 16 , 19 , 20 . As mentioned above, our results showed that s′ and e′ were different between our study groups.…”
Section: Discussionsupporting
confidence: 81%
“…Studies on tissue Doppler imaging (pulsed wave or color coded) indices in patients with the coronary slow flow phenomenon have yielded different results. Although all of these studies were in agreement regarding a′ inasmuch as they reported no difference between patients with the coronary slow flow phenomenon and control groups, some of them showed that s′ and e′ were different between the groups, 13 , 14 , 17 , 18 , 24 and others revealed no difference between the groups 15 , 16 , 19 , 20 . As mentioned above, our results showed that s′ and e′ were different between our study groups.…”
Section: Discussionsupporting
confidence: 81%
“…1 Although various mechanisms have been suggested for the pathogenesis of CSF, the pathophysiology and clinical implications of CSF are not clearly understood. [5][6][7] However, the effect of CSF on left ventricular twist functions has not been assessed. Recent two-dimensional speckle tracking echocardiography (STE) and Doppler studies have shown that CSF results in systolic and diastolic dysfunctions.…”
mentioning
confidence: 99%
“…Therefore, myocardial longitudinal systolic strain rate was the sensitive index in ischemia myocardial, which represented the maximum deformation degree of systole and the contractibility. Recently, the left ventricular longitudinal strain were reported that its significance in the early detection of ischemia myocardial dysfunction in sub-endocardial myocardial, as well as the sensitive index of myocardial contractility of left ventricle [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%